Risk factors, etiology and prognostic markers in patients of young stroke: a prospective observational study - Goel, Divya (International Journal of Research in Medical Sciences, 2023)
Background: The rate of stroke at a young age has accelerated over the years and is a matter of true concern. Young stroke causes devastating consequences leading to loss of productive years and life time disability. Methods: We performed an observational prospective study to identify the risk factors, etiology and prognostic markers in patients of young stroke. Results: The study was conducted on 50 patients who were less than or equal to 50 years and have suffered ischemic stroke during the time period of 6 months i.e. from April, 2022 to September, 2022 and visited Department of Neurology, at SSB heart and multispecialty hospital, Faridabad. We found the prevalence of young stroke was significantly more in males (81%) compared to same aged female participants. Conclusions: Maximum patients suffered young stroke were at an age group 35-45 years. We could identify that the traditional risk factors including diabetes, hypertension and dyslipidemia were the major risk factors compared to the lifestyle based risk factors like smoking or alcohol consumption. The young patients showed similar response to thrombolysis treatment like old stroke patients. All the patients enrolled in the study were cured. Further research is required to understand the risk factors and prognosis of young stroke.